A framework for formulating Malaysia’s public policy through citizen e-Participation - Salamat, Mohamad Aizi; Hassan, Shahizan; Md Fudzee, Mohd Farhan; Ramli, Azizul Azhar (2012)
This paper addresses this key issue by enabling the participation of the citizen in formulating Malaysia’s public policy through e-participation.Currently, there is no e-participation framework for citizen to involve in Malaysia’s public policy formulation. Most public policy formulate by certain group of expertise but the feedback from citizen still lacking. The research embraces the socio-technical research paradigm and uses an Actor-Network Theory (ANT) as the theoretical foundation to explore the mutual interaction between all the actors.The proposed e-participation framework has been validated using Delphi Method and evaluated by experts is shown to be workable and practical.